Assessment of electrocardiographic markers of acute and long‐term hemodynamic improvement in patients with pulmonary hypertension. Issue 5 (26th April 2020) - Piłka, Michał; Darocha, Szymon; Banaszkiewicz, Marta; Wieteska‐Miłek, Maria; Mańczak, Małgorzata; Mańczak, Rafał; Kędzierski, Piotr; Florczyk, Michał; Dobosiewicz, Anna; Torbicki, Adam; Kurzyna, Marcin
Abstract: Background: The remodeling of the right heart in patients with chronic pulmonary hypertension (cPH) is associated with the appearance of electrocardiographic (ECG) abnormalities. We investigated the resolution of ECG markers of right ventricular hypertrophy (RVH) caused by acute and long‐term hemodynamic improvement. Methods: Twenty‐nine (29) patients with chronic thromboembolic pulmonary hypertension (CTEPH) and seven patients with pulmonary arterial hypertension (PAH) were included in the analysis. Patients with CTEPH achieved a significant long‐term hemodynamic improvement following the treatment with balloon pulmonary angioplasty (BPA); all the patients with PAH reported significant acute hemodynamic relief after a single inhalation of iloprost, fulfilling the criteria of responder. Standard 12‐lead ECG was performed before and after intervention. Results: The interval between baseline and control ECG in CTEPH and PAH groups was 28 (IQR: 17–36) months and 15 min (IQR: 11–17), respectively. Despite similar hemodynamic improvement in both groups, only the CTEPH group presented significant changes in most analyzed ECG parameters: T‐wave axis ( p = .002), QRS‐wave axis ( p = .012), P‐wave amplitude ( p < .001) and duration in II ( p = .049), R‐wave amplitude in V1 ( p = .017), R:S ratio in V1 ( p = .046), S‐wave amplitude in V5 ( p = .004), R‐wave amplitude in V5 ( p = .044), R:S ratio in V5 ( p = .004), S‐wave amplitude in V6 ( p = .026), R‐wave amplitude in V6 ( p = .01), and R‐wave amplitude in aVR ( p = .031). In patients with PAH, significant differences were found only for P wave in II (duration: p = .035; amplitude: p = .043) and QRS axis ( p = .018). Conclusions: The effective treatment of cPH ensures improvement in ECG parameters of RVH, but it requires extended time.